THE EFFECT OF VITAMIN D3 ON TOOTH MOVEMENT IN ORTHODONTIC TREATMENT - Wirapradina, Revadya; Indriani, Rezka Indriani; Pandelaki, Refky V.; Pakpahan, Evie Lamtiur (Moestopo International Review on Social, Humanities, and Sciences, 2024)
Malocclusion is a deviation from the position of the tooth from the dental arch outside the acceptable range or normal occlusion. Malocclusion conditions require proper treatment, namely by performing orthodontic treatment. Treatment with orthodontic appliances that can produce tooth movement is expected to align the teeth to achieve esthetics, prevent malocclusion from becoming severe, and return it to a normal occlusion condition. The acceleration of orthodontic tooth movement is currently the subject of various scientific studies aimed at increasing the duration of orthodontic treatment. Purpose: Assessing currently available evidence regarding the effect of vitamin D3 in accelerating orthodontic tooth movement. Methods: The databases PubMed, ResearchGate, Google Scholar, EBSCO were searched from 2012-2023 and searched using the keywords Vitamin D, Canine Distalization, Accelerated Orthodontic Tooth Movement, Bone Remodeling. Conclusion: The majority o of the included studies reported that vitamin D3 can stimulate bone resorption by increasing osteoclast activity which results in the speed of bone resorption resulting in an increase in the speed of tooth movement and helps in stabilizing orthodontic tooth movement.